Optimization of Strategic Communication of the Center for Islamic History Studies of Lampung in the Development of the Islamic Civilization History Study Program UIN Raden Intan Lampung - Wahyu Iryana; Muhamad Bisri Mustofa; Fegi Sentiana (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
In the context of the development of the Islamic Civilization History Study Program, several challenges need to be overcome. One is the need to optimize strategic communication of the Lampung Center for Islamic History Studies as an integral part of the study program development efforts. Although the Lampung Center for Islamic History Studies has potential and resources, governance, transparency, and communication effectiveness challenges can affect the progress and quality of the study program. This study uses a qualitative research method consisting of a series of approaches to explore the Lampung Center for Islamic History Studies communication strategy in the development of the Islamic Civilization History Study Program at UIN Raden Intan Lampung, namely Participatory Interviews and Observations. Strategic communication optimization is the key to success in developing the Islamic Civilization History Study Program at UIN Raden Intan Lampung. Through a planned and effective communication approach, the Lampung Center for Islamic History Studies can achieve the goal of developing a better and sustainable study program. Improving the quality of research and publications is one of the positive impacts of optimized strategic communication. By developing a good communication strategy, the resulting research becomes more quality and relevant, and the results can be widely published, improving academic reputation and attracting the interest of students and other researchers